Transcatheter mitral valve in ring, hazards of long anterior mitral leaflet and 3‐dimensional rings. Issue 2 (31st August 2020) - Sekaran, Nishant; Horne, Benjamin D.; Doty, John R.; Reid, Bruce B.; Miner, Edward C.; Harkness, James R.; Jones, Kent W.; Minder, Camille Michael; Caine, William T.; Clayson, Stephen E.; Whisenant, Brian K.
Abstract: Objectives: The purpose of this study was to define anterior mitral leaflet (AML) length and mitral ring characteristics associated with LVOT obstruction and PVL following MViR. Background: Transcatheter Mitral Valve in Ring (MViR) procedural complications including parvalvular leak (PVL) and left ventricular outflow tract (LVOT) obstruction are frequent. Methods: Clinical records, computer tomographic scans (CTs) and echocardiograms of consecutive MViR patients were retrospectively reviewed for anterior mitral leaflet length, CT‐simulated neoLVOT, and aortomitral angle among patients with and without MViR‐induced LVOT obstruction. Acute and 1‐year outcomes are described. Results: Twenty‐two patients underwent MViR. Technical success was achieved in 13/22 (57.1%) patients, limited by paravalvular regurgitation requiring second transcatheter heart valves (THVs) in seven patients. Second valves were needed in 6/11 (54.5%) patients with 3‐dimensional rings but 1/11 (9.1%, p = .06) of patients with planar rings. Procedure success at 30 days was achieved in 20/22 (90.9%) patients. There were no procedural, in‐hospital, or 30‐day deaths. Two patients developed significant LVOT obstruction, one managed with urgent surgery and one with elective alcohol septal ablation. Anterior mitral leaflets were longer among the two patients with LVOT obstruction than the 20 patients who did not develop LVOT obstruction when measured by TEE (30 mm vs. 21 mm, p = .009) or by CT (29 mm vs. 22 mm, p = .026). Conclusions: AML >25 mm increases the risk of MViR induced LVOT obstruction. PVL is common, particularly in 3‐dimensional rings which can be managed with a second THV.